TINJAUAN HUKUM ISLAM TERHADAP JUAL BELI PRODUK SATANISME DI VENOM METAL DISTRO JL. GAJAH MAGERSARI SIDOARJO - Muhamad Reza Noviansyah (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2016)
Essay with title â€œOverview of Islamic Law Against The Practice of Selling and Buying Satanism Products in Venom Metal Distro Jalan Gajah Magersari Sidoarjoâ€, is the result of field research to know about the practice of selling and buying Satanism products in Venom Metal Distro and how Islamic Law review of this practice.To answer these question, is used type of field researchwith qualitative methods. To collect data is used technics of observatition, interview and literature studies. Data, is obtained and analyzed by descriptive analysis, describes the practice of selling and buying products in Islamic Law, Sadd al Dhariâ€™ah and definition of Satanism itself and how practice of selling and buying Satanism products in Venom Metal Distro. Inductive paradigm is used by.Based on the result, the writer concluded that the practice of selling and buying products in Venom Metal Distro appropriated to Islamic Lawâ€™s practice of selling and buying products, because the product, the place and the buyer are cleared and real. But it is just against to Islamic Law because of Satanism product. The products were contained by Satanism and Atheism. Object themed of the products are metal, black metal, death metal, underground who have not only hardcore genre but also Satanism and Atheism lyrics. Islamic law reviews that this practice is not appropriate,because the product is not suitable to rukun and syariâ€™ah Islam. The writer concluded that the practice of selling and buying Satanism products in Venom Metal Distro is makhruk and can be haram if mafsadah of the Satanism is harder than maslahah. According to the conclusion, the writers suggest to seller, buyer and owner, before the products were saled to buyer, more wiser to explain and to suggest not to keep Satanism as faith. Itâ€™s used only for hobby, not to keep it and moreover follow the ritual.